NUMERICAL ANALYSIS ON THE PROPAGATION OF ULF/ELF SIGNALS IN THE LITHOSPHERE WITH HIGHLY CONDUCTIVE LAYERS - Kulchitsky A.V.; Ando Y.; Hayakawa M. (My University, 2004)
This paper deals with the numerical analyses on the effect of inhomogeneities (highly conductive layers) on the propagation of seismogenic electromagnetic signals in the ULF/ELF range. For simplicity of computations we assume that the geometrical configuration is uniform in one direction, which is possibly consistent with the actual situation. We adopt the frequency domain finite difference method in the computation, and calculate the electric field at points where the fields are measurable. Our numerical results show some significant findings: (1) it is necessary to consider the presence of air region in the lithospheric propagation, (2) there exist characteristic frequencies at which we have the effective response at a point due to the presence of the conductive layer, (3) a site closest to the source does not necessarily show the strongest response, depending on the configuration of the layers.